Socio-economic and political responses to regional polarisation and socio-spatial peripheralisation in Central and Eastern Europe: a research agenda - Lang, Thilo (Hungarian Geographical Bulletin, 2015)
In the past years, new patterns of regional disparities between metropolised core regions and the remaining parts of Central and Eastern European countries (CEE) have emerged. Such spatial disparities have lately fuelled concerns about further regional polarisation and the peripheralisation of non-metropolitan regions in particular. This is the case although balancing spatial development has been a major goal of European Regional Policy. The paper argues that there is a clear need to bett er understand the social, economic, discursive and political processes constituting regional polarisation and to conduct further research on approaches to deal with and respond to peripheralisation. The proposed research agenda focuses on a multi-scalar relation between core and peripheral regions and applies a process based dynamic understanding of peripherality and centrality. Following this, peripheralised regions bear agency capacities and cannot be seen as powerless victims of some overarching processes associated with the globalising economy. Applying the notions of polarisation and peripheralisation to guide further research, offers multi-dimensional, multi-scalar and process based conceptualisations of regional development research. With the proposed research agenda, I would like to open up the discussion on new interpretations of the terms peripherality and centrality, rurality and urbanity, border and rural areas, core and peripheral regions, and contribute to the development of new approaches in multi-level governance and ultimately in regional policy.